How Do Acupuncture and Moxibustion Act? - Focusing on the Progress in Japanese Acupuncture Research - - Kenji Kawakita; Hisashi Shinbara; Kenji Imai; Fumihiko Fukuda; Tadashi Yano; Kinya Kuriyama (Elsevier, 2006)
Abstract.: The mechanisms of action of acupuncture and moxibustion as reported by Japanese researchers are reviewed. The endogenous opioid-mediated mechanisms of electroacupuncture (EA) as used in China are well understood, but these are only one component of all mechanisms of acupuncture. These studies emphasize the similarity of the analgesic action of EA to various sensory inputs to the pain inhibition mechanisms. In Japanese acupuncture therapy, careful detection of the acupuncture points and fine needling technique with comfortable subjective sensation are considered important. The role of polymodal receptors (PMR) has been stressed based on the facts that PMRs are responsive to both acupuncture and moxibustion stimuli, thermal sensitivity is essential in moxibustion therapy, and the characteristics of acupuncture points and trigger points are similar to those of sensitized PMRs. Acupuncture and moxibustion are also known to affect neurons in the brain reward systems and blood flow in skin, muscle, and nerve. Axon reflexes mediated by PMRs might be a possible mechanism for the immediate action of acupuncture and moxibustion. Reports on the curative effects of acupuncture on various digestive and urological disorders are also reviewed briefly. Keywords:: acupuncture and moxibustion, polymodal receptor, endogenous opioid, reward system, somato-autonomic reflex